2022
DOI: 10.1055/a-1978-6753
|View full text |Cite
|
Sign up to set email alerts
|

Food intolerance in patients with functional abdominal pain: Evaluation through endoscopic confocal laser endomicroscopy

Abstract: Background and study aims Gastrointestinal symptoms assumed by food intolerance are reported frequently in the general population. There is a significant difference between self-reported and objective proven food intolerance as shown by placebo controlled double blind randomized trials. This discrepancy may be overcome by endoscopic confocal laser endomicroscopy (eCLE). Patients and methods In an observational study we evaluated 34 patients with functional abdominal pain and adverse reaction to food by eCLE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
2
10
2
Order By: Relevance
“…Only one patient showed this phenomenon. This is in contrast to other studies where up to 50 % of patients with disorders of the gut brain barrier had "leaky gut" [14,15]. This finding suggests that fluorescein leakage into the duodenum during eCLE is not a nonspecific phenomenon because the methodological approach in our investigated patients was the same as reported in the other groups [14,15].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Only one patient showed this phenomenon. This is in contrast to other studies where up to 50 % of patients with disorders of the gut brain barrier had "leaky gut" [14,15]. This finding suggests that fluorescein leakage into the duodenum during eCLE is not a nonspecific phenomenon because the methodological approach in our investigated patients was the same as reported in the other groups [14,15].…”
Section: Discussioncontrasting
confidence: 92%
“…This is in contrast to other studies where up to 50 % of patients with disorders of the gut brain barrier had "leaky gut" [14,15]. This finding suggests that fluorescein leakage into the duodenum during eCLE is not a nonspecific phenomenon because the methodological approach in our investigated patients was the same as reported in the other groups [14,15]. In addition, the low rate of "leaky gut" of the duodenal mucosa in our study suggests that the postulated epithelial barrier dysfunction in EoE is limited to the esophageal epithelium and not found in other parts of the gastrointestinal tract.…”
Section: Discussioncontrasting
confidence: 91%
“…Standardized eCLE (Cellvizio System, Mauna Kea Technologies, 9 rue d Enghien, 75010 Paris, France) was applied as previously reported [6,7,8,12]. The investigations were carried out during conventional upper GI endoscopy after an eight hour fasting peri-od under propofol sedation.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical tools for detecting GARF comprise nutrition diary, identification of lactose, fructose, sorbit and histamine intolerance, food allergies, mast cell disturbances, and elimination diets, respectively. In recent studies, it has been shown that endoscopic confocal laser endomicroscopy eCLE) can provide an objective measure to test mucosal reaction to duodenal food challenge (DFC), [6,7,8]. Duodenal mucosal application of specified food via the endoscope channel may induce immunemediated fluid extravasation through epithelial leaks together with cell shedding as detected by leakage of intravenously applied fluorescein into the duodenal lumen [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…First, we would like to address some specificity and technical issues. The presence of leakiness of fluorescence into the lumen using CLE has been reported repeatedly in disorders of gut-brain interaction: patients without PLE but instead with irritable bowel syndrome or functional dyspepsia [2,3,4]. One group found that gaps per 1000 epithelial cells in the duodenum correlated with intestinal permeability in patients with functional dyspepsia [4].…”
mentioning
confidence: 88%